Modeling and Control of an Induction Motor With Built-in Force Actuator for Vibration Suppression - Muhammad Numan; Sadjad Madanzadeh; Jawad Tariq; Olli Liukkonen; Gyan Ranjan; Firdausa Ahmed; Tuomo Lindh; Niko Nevaranta (IEEE Access)
Lateral vibrations are occurring in rotating machinery and can limit operational performance and range. Such vibrations often lead to instability, decreased precision, and potential damage to the system. However, by integrating force actuators directly within the electrical machine, it becomes possible to actively suppress these vibrations, enhancing system stability and extending its operational speed limits. This paper focuses on the modeling and control of an induction machine equipped with in-built force actuator to suppress lateral vibrations. The studied electrical machine concept involves a structure with separate winding sets; one for suspension and another for motoring. Through a selected simulation case involving a rotor system, it is demonstrated how the inclusion of force actuators allows for the suppression of the dominant vibration modes. As a result, the approach effectively extends the operational range of the induction machine, offering a more stable and reliable solution for high-speed applications. The proposed model and control strategy are analyzed with a detailed simulation model, supported by a robustness analysis of the controller under model uncertainties.